Psycholinguistics : a resource book for students - Field, John, 1945-. (London : Routledge, 2003)
The books in this series cover core areas of language study and are one-stop resources for students. Assuming no prior knowledge, they offer an accessible overview of the subject, with activities, study questions, commentaries and key readings.
Includes bibliographical references and index.
Keywords: Psycholinguistics